PERANCANGAN SISTEM INFORMASI INVENTORY MENGGUNAKAN METODE EXTREME PROGRAMMING BERBASIS WEB - Zakkiyatul Mardiya; Agung Perdananto (CV. Multi Kreasi Media, 2024)
Inventory Goods are always needed in the company's activities. The existence of inventory on the one hand is a waste so that it can be said as a burden that must be eliminated but on the other hand it is very necessary to ensure the smooth fulfillment of demand because if there is no supply then the need will not be met. Doing it manually causes many difficulties for managers so that every time there is an entry or exit of goods, the officer must reopen the book in the workshop. So it takes a little more time to do this. Buyers will feel a little dissatisfied with the time-consuming service. Generally, when a buyer comes to make inquiries about the goods to be sought, both in terms of brand, price and model, when the supplier stocks the goods, it is necessary to record detailed data. With this web-based inventory information system, Agus Injection Motor Workshop can make it easier for admins to obtain available item data. Information system to provide administrative convenience in storing and processing data to facilitate performance in operations.